Plasma cell dyscrasias - Roccaro, Aldo M.; Ghobrial, Irene M. (Cancer treatment and research, 2016)
This book provides a concise overview of the state of the art in the biology and treatment of plasma cell malignancies, a heterogeneous group of diseases primarily characterized by the presence of clonal plasma cells within the bone marrow or extramedullary sites. The plasma cell dyscrasias investigated include monoclonal gammopathy of undetermined significance (MGUS), multiple myeloma, plasmacytoma, immunoglobulin deposition diseases (primary amyloidosis and systemic light and heavy chain deposition diseases), and Waldenström’s macroglobulinemia. In the case of multiple myeloma, the coverage ranges from genomic aberrations and microRNAs to treatment for different patient groups, upcoming novel therapies, immunotherapy, and transplantation. The book reflects the significant research advances achieved in this field during the past few years, which have enhanced our understanding of the molecular mechanisms responsible for the pathogenesis of plasma cell dyscrasias